Increasing Level of Leisure Physical Activity Could Reduce the Risk of Hip Fracture in Older Women: A Dose–Response Meta-analysis of Prospective Cohort Studies. Issue 11 (March 2016) - Rong, Ke; Liu, Xiao-yu; Wu, Xu-hua; Li, Xiao-liu; Xia, Qing-quan; Chen, Jiong; Yin, Xiao-fan
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: We carried out the study to investigate and quantitatively assess the potential association between current level of physical activity and the risk of osteoporosis hip fracture in older women. Relevant publications before October 2015 were identified using the PubMed and Ovid searching tools. A dose–response meta-analysis was carried out to combine and analysis results. Fourteen prospective studies were included in the meta-analysis. A general analysis of 9 studies showed a significant inverse relationship between increasing level of physical activity and risk of hip fracture in older women [relative risk (RR) = 0.93, 95% confidence interval (95% CI): 0.91–0.96]. The result of a sensitivity analysis was consistent with the general analysis (RR = 0.94, 95% CI: 0.93–0.96). The association between increasing level of physical activity and risk of wrist fracture was not statistically significant in a general analysis of three studies (RR = 1.004, 95% CI: 0.98–1.03). A potential direct association between increasing level of physical activity and risk of wrist fracture was observed after removing 1 study with the greatest weight (RR = 1.01, 95% CI: 1.00–1.03). No significant publication bias was observed in our analysis. Our results show that increasing level of physical activity within an appropriate range may reduce the risk of hip fracture but not the risk of wrist fracture in older women.